2021
DOI: 10.3390/ijms222011086
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Noradrenergic System in Eating Disorders: A Systematic Review

Abstract: Noradrenaline (NE) is a catecholamine acting as both a neurotransmitter and a hormone, with relevant effects in modulating feeding behavior and satiety. Several studies have assessed the relationship between the noradrenergic system and Eating Disorders (EDs). This systematic review aims to report the existing literature on the role of the noradrenergic system in the development and treatment of EDs. A total of 35 studies were included. Preclinical studies demonstrated an involvement of the noradrenergic pathw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 79 publications
(118 reference statements)
0
14
0
Order By: Relevance
“…The mechanism of action of phentermine is not fully understood; however, it is known that phentermine induces norepinephrine (NE) and dopamine release by inhibiting its recapture in the hypothalamus [ 32 , 33 ]. In the rat model, NE injection into the hypothalamus was found to reduce food consumption, while NE depletion caused by ascending ventral NE axon lesions led to overeating, thus suggesting that NE promotes satiety [ 34 , 35 ]. However, other studies suggest an opposite effect of exogenous NE in the hypothalamus, decreasing satiety in rats [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of action of phentermine is not fully understood; however, it is known that phentermine induces norepinephrine (NE) and dopamine release by inhibiting its recapture in the hypothalamus [ 32 , 33 ]. In the rat model, NE injection into the hypothalamus was found to reduce food consumption, while NE depletion caused by ascending ventral NE axon lesions led to overeating, thus suggesting that NE promotes satiety [ 34 , 35 ]. However, other studies suggest an opposite effect of exogenous NE in the hypothalamus, decreasing satiety in rats [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review identified a series of key data on the relationship between the noradrenergic system and EDs. Besides its relevant direct, hypothalamus-based actions on feeding regulation, the noradrenergic system is indirectly implied in various endocrine networks controlling human nutrition [64]. Dopamine is a neurotransmitter that regulates the rewarding nature of food [65].…”
Section: Biochemicalmentioning
confidence: 99%
“…Our observed effects from the dietary conditions were more pronounced with the use of selective norepinephrine or dopamine reuptake inhibitors. Alterations in the noradrenergic system have been implicated in binge eating pathologies (Pruccoli et al ., 2021). One of our major findings of this study was that a high dose of nisoxetine (5 mg/kg) resulted in a diminished response to the startle pulse (110 dB) in the RB group compared with the control (N) group under standard chow conditions.…”
Section: Discussionmentioning
confidence: 99%